Effect of irrigation and potash levels on growth, yield and quality of spring sugarcane (Saccharum officinarum) - BHATT, RAJAN; SINGH, JAGDISH; KASHYAP, LENIKA (The Indian Journal of Agricultural Sciences, 2022)
I1 plots had higher germination (5.61%), millable canes (9.09%), brix (5.19%), yield (0.6%) and CCS (t/ha) (2.35 and 4.37% at 10th and 12th months), respectively. K3 plots reported significantly higher performance as compared to K1 and K2 treatments while being at par with the K4 treatment. Benefits were reported to be highest at K3 treatment under water stressed conditions. Hence, 80 kg K2O/ha under water stressed and potash deficient soils prove to be a better option for better cane growth, yield and quality parameters.